HABITAT DAN POPULASI KERBAU LIAR (Bos bubalus) DI DESA MAKATIAN KECAMATAN WERMAKTIAN KABUPATEN MALUKU TENGGARA BARAT - John . F. Sahusilawane (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2017)
The habitat and population the wild buffalo (Bos bubalus) in the village Makatian, in the district Wermakatian, sinister western district Maluku Tenggara Barat. The purpose of this research was to know the habitat and population of wild buffalo (Bos bubalus) in the vilage Makatian, in the district Wermakatian, sinister western district Maluku Tenggara Barat. The purpose by used Pellet Group Counts Method which the population density was know by faeses accumulation then, regression analysis used to fount the teletion between the vegetation density, variety of vegetation and the population of Bos bubalus.